Synthesis and Characterization of Graphene Thin Films by Chemical Reduction of Exfoliated and Intercalated Graphite Oxide - F. T. Thema; M. J. Moloto; E. D. Dikio; N. N. Nyangiwe; L. Kotsedi; M. Maaza; M. Khenfouch (Journal of Chemistry)
Commercial flakes of graphite were prepared into functionalized graphene oxide (GO) by chemical treatment. After the exfoliation and intercalation of graphene into functionalized graphene oxide that formed stable colloidal dispersion in polar aprotic solvent, the reduction process was undertaken by continuous stirring with hydrazine hydrate. The reduced material was characterized by X-ray diffraction (XRD), attenuated total reflectance (ATR) FT-IR, ultraviolet visible (UV-vis), atomic force microscopy (AFM) and Raman spectroscopy which confirm the oxidation of graphite and reduction of graphene oxide into graphene sheet.